Synthesis of Ce-Mesoporous Silica Catalyst and Its Lifetime Determination for the Hydrocracking of Waste Lubricant - Wega Trisunaryanti; Triyono Triyono; Iip Izul Falah; Andreas David Siagian; Muhammad Fajar Marsuki (Universitas Gadjah Mada, 2018)
The synthesis of Ce/mesoporous silica (Ce/MS) and its lifetime determination for the hydrocracking of waste lubricant has been carried out. The MS was synthesized using tetraethyl orthosilicate (TEOS) and gelatin extracted from bovine bone as a template. Cerium was impregnated onto the MS by wet impregnation method using Ce(NO3)3.6H2O. The MS and Ce/MS were then characterized by means of acidity using ammonia base vapor adsorption, Fourier Transform Spectrophotometer (FTIR), Transmission Electron Microscope (TEM), Scanning Electron Microscope-Energy Dispersive X-ray Spectrometer (SEM-EDX), and surface area analyzer (SAA) based on the BET and BJH equation. The Ce/MS catalyst was tested in hydrocracking of waste lubricant in three runs. Lifetime of Ce/MS catalyst was determined using a linear regression of the liquid product yields vs hydrocracking time. The Ce/MS catalyst showed an acidity of 2.79 mmol/g, BJH desorption pore diameter of 3.84 nm, BET surface area of 246.55 m2/g, and total pore volume of 0.44 cm3/g. The yield of liquid product obtained from hydrocracking of waste lubricant using the Ce/MS catalyst for the first, second, and third runs was 21.42, 17.23 and 10.54 wt.%, respectively for 2.5 h per each run. Lifetime of Ce/MS catalyst in hydrocracking of waste lubricant was 12.54 h.